1376 Latex Allergies: Seeking an Alternative to Minimise Risk in The Operating Theatre. (12th October 2021) - Zargaran, A; Zargaran, D; Ashraf, M; Khanal, P; Srivastava, A; Mosahebi, A
Abstract: Introduction: Natural Rubber Latex (NRL) gloves have been ubiquitously used in surgical practice. Over the past few decades, there have been many reports of NRL allergies associated with their use presenting a safety hazard to both patients and healthcare workers. Powder-free and latex-free gloves have been shown to offer reductions in incidence of allergic reactions, as well as cost savings. Method: We performed a literature search to identify the rates of reaction to latex across the population in addition to the associated costs including litigation costs, costs of admission, and lost work time associated. We further looked at the rates of perforation of alternatives and the costs associated with such a transition. Results: The UK prevalence of sensitisation amongst healthcare workers has been estimated to be 10%. The average cost of litigation to the employer was found to be $21, 402 per claim. The mean cost of inpatient care for anaphylaxis has been cited as £469.88, with additional costs such as follow-up representing approximately £400. A 14-month study found cost savings of $10, 000pa with a switch to non-latex gloves. Furthermore, an overall perforation rate of 80% in a latex-free glove compared to 34.4% in a latex glove. Conclusions: From a business perspective, there is evidence of cost-savings arising from a switch to latex-free gloves, however, formal cost-effectiveness analyses would inform future decisions. Furthermore, comfort and reducing the chances of allergic reactions through removing the offending allergen all represent benefits of switching to latex-free gloves, however, non-inferiority analyses will inform future strategies both locally and nationally.